Policy Administration in Strengthening the Economic Value of Creative Products Based on Community - Anita Syam; Hasnawati Ummu; Andi Asdar; Mashuri Mashuri; Feby Triadi (Public Resource Innovation Management and Excellence, 2025)
Strengthening mark economy results creation-based community is issue strategic in policy administration public, especially in context development sustainable and economic creative Although regulations national has confess importance advancement culture and economy creative, implementation policy administrative at the level area Still face various challenges, especially in integration protection right communal, facilitation business and distribution benefit fair economy. Research​ This aim analyze design and implementation policy administration in strengthen mark economy results creation-based community with use approach qualitative through studies policy and design studies multi-level case. Data obtained through interview in depth analysis document policies and observations limited, then analyzed use technique analysis thematic. Framework analysis integrates theory Public Value, Collaborative Governance, and New Public Governance. Research Results show that strengthening mark economy Not Enough done through approach sectoral and administrative conventional but rather need reconstruction design creation - oriented policies​ mark public, institutionalization of governance collaborative, as well as guaranteed justice distribution benefit economy. The gap between regulatory norms and practice implementation becomes obstacle main in optimization potential economy culture. Therefore that, reformulation policy administration need put community as actor main through mechanism participatory, integration protection right communal, as well as strengthening capacity institutional. This study contributes to development literature administration public with confirm importance multidimensional approach to governance​ economy culture-based community.